The Scandinavian Sarcoma Group Skeletal Metastasis Registry: functional outcome and pain after surgery for bone metastases in the pelvis and extremities. - Hansen BH; Keller J; Laitinen M; Berg P; Skjeldal S; Trovik C; Nilsson J; Walloe A; Kalén A; Wedin R (Acta Orthopaedica (Supplement))
Background Few authors have investigated function and pain after surgical treatment of patients with bone metastases. In 1999 the Scandinavian Sarcoma Group (SSG) initiated the Skeletal Metastasis Registry as a multi-centric, prospective study to provide a scientific basis for recommendations of treatment. Patients and methods We have analyzed function and pain in 530 patients ( mean age 65 yr) operated on ( 599 operations) for non-spinal skeletal metastases at 9 SSG centres. 7% were operated for more than 1 metastasis. Carcinoma of the breast, prostate, kidney, and lung were the dominating sites for primary tumors. Results 25% of the patients died within 6 weeks after operation. 11% of the patients had complications. 6% had reoperation. In patients surviving more than 1 year the reoperation rate was 12%. 92% of the patients had no, light or moderate pain from metastasis at 6 weeks ( first control) and 6 months follow-up. Patients using opioids were reduced from 40% preoperative to 30% at 6 months after surgery. In patients with metastases in pelvis or lower extremity 79% were walking with or without crutches, 6 weeks and 88%, 6 months after surgery. More patients with metastases in proximal femur were mobile at 6 weeks and 6 months when treated with prosthetic replacement compared to internal fixation. Interpretation Palliative surgery for bone metastases improves function and reduce pain. Mobility is improved by surgery in patients with metastases in the pelvis or lower extremity. Prosthetic replacement seems to do better than internal fixation for metastases in the proximal femur. We need to analyze function and pain earlier than 6 weeks postoperative to investigate the benefit of surgery in patients with short time survival.